Genetic Diversity of Black Pepper in Bangka Island Based on SSR Markers - Prayoga, Gigih Ibnu; Salmi; Saputra, Herry Marta; Mustikarini, Eries Dyah; Derajat, Alfan (HAYATI Journal of Biosciences, 2026)
The Bangka Belitung Islands Province is a major centre of black pepper production in Indonesia. Black pepper production in Indonesia has dropped, so it needs to be increased using superior varieties. Identifying the genetic diversity of black pepper plants is important for breeding superior varieties. The study's objective was to determine the genetic diversity and relationships of Bangka landrace black pepper using SSR markers. This research was conducted from June to August 2024 at the Biology Laboratory, Universitas Bangka Belitung. The black pepper genotypes used in this study were as follows: Lampung Daun Kecil (LDK), Nyelungkup, Petaling 1, Chunuk, Peremis, Balunijuk 1, Balunijuk 2, and Jerambah Gantung. The SSR markers employed in this study included Psol3, Psol6, Psol9, Psol10, Psol11, Psol17, and Psol19. The genetic relationship of Bangka black pepper was analysed using the UPGMA method. Genetic relationship revealed two main clusters of eight Bangka black pepper genotypes. Cluster I consisted of the Peremis and Balunijuk 2 genotype, while the remaining six genotypes were contained within cluster II. The structure population exhibited two subpopulations, with FST values of 0.30 and 0.61, respectively. The results showed that the seven primers used produced polymorphic (82.1%) and monomorphic (17.9%) bands on eight pepper genotypes. The Polymorphic Information Content (PIC) value of all primers tested was found to be medium, with the exception of Psol9, which exhibited a low PIC value. The average PIC value was 0.32, which is categorized as medium.